Real-life functioning and duration of illness in schizophrenia: A mediation analysis - C. Brasso; S. Bellino; P. Bozzatello; C. Montemagni; P. Rocca (Heliyon)
Patients with schizophrenia (SZ) often experience difficulties and impairment in daily functioning. Various factors influence functional outcomes, such as the duration of illness (DOI), the intensity of symptoms, and cognitive impairments. This study aimed at assessing the total, direct, and indirect contribution of the DOI to three key areas of daily functioning for individuals with stable SZ: life skills, work abilities, and interpersonal relationships.Spearman's partial correlations, adjusted for age, gender, and education, were computed between the DOI, symptoms and cognitive variables, and the three real-life functioning domains. We performed three generalized linear mediation models, one for each selected domain of functioning as the dependent variable. Symptoms and cognitive variables significantly correlated with the DOI and at least one of the functioning domains were included in the mediation models as possible mediators between the DOI and the domain of real-life functioning with which they were correlated. The DOI was the independent variable in all models. Effects were computed in total, direct, indirect, and component-estimated forms. A p-value of < .05 was considered statistically significant.A longer DOI was associated with poorer everyday life and working skills, while no such link was found with interpersonal relationships. The negative effect of the DOI on everyday life and working skills was mediated by disorganization and metacognitive mastery and disorganization alone respectively. Early targeted interventions on disorganization and metacognitive mastery might lead to improvements in the functional outcomes of people living with SZ.